THE AFFECTING ANEMIA OCCURRENCE FACTORS IN PREGNANCY IN SINGKAWANG CITY - Yully Asmariana; Nursyam Perwitasari; Evi Andriani (Jurnal Kesehatan Prima, 2018)
Abstract: Anemia is a common health problem during pregnancy. Anemia can cause complications in pregnancy and increase maternal mortality (MMR). The maternal mortality Kota Singkawang reaches 306 / 100,000 live births. In the year 2014 the number of maternal deaths in the city of Singkawang about 80% among them due to bleeding and other causes. This study aims to determine the affect of the incidence of anemia in pregnancy in the city of Singkawang. The method used in this research is cross-sectional study. The data factors processed in univariate with frequency number table, bivariate with cross table 2 X 2 and tested with chi square. While the amount of risk is measured by Odds Ratio. The number of samples is 210 pregnant women taken by simple random sampling. The result of the research was 57.1% of respondents who had anemia. The result of bivariate analysis found that from 4 variables studied, there were 4 variables related to the incidence of anemia that is education (p = 0,0475, OR = 2,000), the number of ANC visits (p = 0.047, OR = 2,000), the parity (p = 0,341, OR = 1,336), the pregnancy distance (p = 0,556 , OR = 0.813). Therefore, to suppress the incidence of anemia in pregnancy and its various effects it is advisable to regulate pregnancy through family planning programs, as well as to note the increase of ANC visits.Keywords: Education, parity, number of ANC visits, pregnancy distance, and anemia.